1988
DOI: 10.1093/ajcp/89.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Studies of Peripheral Blood of Neonates with Down’s Syndrome and Transient Abnormal Myelopoiesis

Abstract: Ultrastructural studies were performed on blood samples from five neonates with Down's syndrome and transient abnormal myelopoiesis (TAM). Three methods of fixation were employed to detect diaminobenzidine (DAB) reactivity. The first method used glutaraldehyde solution, while the second and third methods used tannic acid-glutaraldehyde mixtures. Before fixation by the second method, specimens were washed in order to eliminate plasma, and before fixation by the third were diluted to lessen the effects of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of surface and ultrastructural markers has shown that the transiently proliferating cells include a major megakaryocytic or megakaryoblastic component (3, [7][8][9][10], and this finding has been linked with previous knowledge that cases of acute leukemia presenting in older infants and children with Down syndrome include a disproportionately large number with megakaryoblastic leukemia (11)(12)(13). Zipursky et al (2) conclude that the available evidence suggests that the transient form of leukemia occurring in newborn infants with Down syndrome is acute megakaryoblastic leukemia in which there is a high rate of spontaneous regression.…”
Section: Introductionmentioning
confidence: 99%
“…The use of surface and ultrastructural markers has shown that the transiently proliferating cells include a major megakaryocytic or megakaryoblastic component (3, [7][8][9][10], and this finding has been linked with previous knowledge that cases of acute leukemia presenting in older infants and children with Down syndrome include a disproportionately large number with megakaryoblastic leukemia (11)(12)(13). Zipursky et al (2) conclude that the available evidence suggests that the transient form of leukemia occurring in newborn infants with Down syndrome is acute megakaryoblastic leukemia in which there is a high rate of spontaneous regression.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating blasts in these patients were found to be quite heterogeneous in ultrastructural morphology and cytochemistry (Bessho et al, 1988), consisting of cells of megakaryocyte, granulocyte, and erythroid series.…”
Section: Discussionmentioning
confidence: 95%
“…Transient myeloproliferative disorder associated with trisomy 21 receives several other names throughout the literature reviewed: transient abnormal myelopoiesis [2,18], leukemoid reaction [&8, 101, transient leukemia [3] , and transient leukemoid proliferation [9].…”
Section: Discussionmentioning
confidence: 99%